An insight to the cleavage of Β-carotene to vitamin A: a molecular mechanics study - Mohamed, N.; Zain, Sharifuddin Md; Rahman, N.A.; Hashim, R. (2001)
The conversion mechanism of β-carotene to vitamin A has been a topic of much discussion for many years since the first proposal of central cleavage mechanism, which was soon challenged by arguments supporting the eccentric cleavage mechanism. Inconclusive evidences have led to the proposal that the conversion of β-carotene does take place through both these mechanisms, possibly by different oxygenase enzymes at different locations in the body. In order to have further insight and better understanding of the cleavage mechanism, molecular mechanics calculations were performed on several cis- and trans-conformations of β-carotene at different polyene portion. The results indicated a series of relatively low energy cis-conformers in addition to the all trans-conformer with lowest energy conformation being the cis-C9′-C10′ double bond (E = 46.46 kcal/mol in water) which could act as the possible starting conformer for the reaction. The molecular mechanics (MM) energy of various cyclic peroxide structures was also carried out and the results seem to support the formation of vitamin A via a systematic degradation of β-carotene. © 2001 Elsevier Science B.V.